STUDIES OF ICE ETCHING. I. APPLICATION OF THERMAL ETCHING TO THE STUDY OF SURFACE ABRASION IN ICE CRYSTALS. - Kuroiwa,Daisuke (1965)
Thermal etching of ice and its application to the investigation of surface abrasion in ice crystals is explained. Investigations of surface abrasion in ice crystals provide fundamental information in the study of snow and ice friction. The technique of producing evaporation etch pits by the application of Formvar film to the ice crystal surface is described, and the development of microcrystals by recrystallization is compared with the surrounding mother crystals. Experimental data are presented and discussed with emphasis on the development of thermal etch pits, scratches on different crystal faces, damage to the prismatic face, thermal etch channels on the basal plane, predominant orientation of etch channels on the basal plane, and etch-pit-free zones and stress concentrations around solid inclusions. (Author) Prepared in cooperation with the Institute of Low Temperature Science, Hokkaido Univ., Sapporo (Japan).